Development of KOMAT: A Problem-Based Learning Comic Media to Enhance Students’ Motivation and Learning Outcomes in Mathematics - Annisa Nur Hasanah; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
This study aims to develop and assess the effectiveness of KOMAT (Mathematics Comic Media) integrated with a Problem-Based Learning (PBL) approach to improve students' motivation and learning outcomes in the topic of Systems of Linear Equations in Two Variables (SPLDV). The research employed the ADDIE development model consisting of analysis, design, development, implementation, and evaluation phases. The product was validated by material and media experts and tested on 28 eighth-grade students at SMP Negeri 42 Medan. Research instruments included expert validation sheets, pretest and posttest assessments, and student response questionnaires. The validation results showed that KOMAT was highly valid, with a score of 97% from material experts and 94% from media experts. Learning outcomes improved significantly, with average scores increasing from 59% (pretest) to 88% (posttest), yielding an N-Gain of 0.71 in the high category. Furthermore, student responses averaged 88%, indicating very good engagement and motivation. These findings suggest that KOMAT is a pedagogically effective and engaging media that supports conceptual understanding and learner motivation in mathematics. Future research is recommended to explore broader applications across topics and digital formats.